Neuroprotective effect of Ziziphi Spinosae Semen on rats with p-chlorophenylalanine-induced insomnia via activation of GABAA receptor - Xiao, Fengqin; Shao, Shuai; Zhang, Hongyin; Li, Guangfu; Piao, Songlan; Zhao, Daqing; Li, Guangzhe; Yan, Mingming (Frontiers in Pharmacology, 2022)
Ziziphi Spinosae Semen (ZSS), as the first choice of traditional Chinese medicine in the treatment of insomnia, has attracted extensive attention. However, the current studies on improving sleep mechanism of ZSS are mainly focused on the role of single component, to further reveal the potential mechanism of ZSS in multi-constituents is necessary. In this study, ZSS extract (ZSSE) was extracted from ZSS via detailed modern extraction, separation and purification technologies. The chemical constituents of ZSSE were analyzed by HPLC-MS. In vivo experiments, rat’s model induced by p-chlorophenylalanine (PCPA) has been established to investigate the potential effect and corresponding mechanism of ZSSE on improving sleep. HE stains experimental results indicated that the drug group showed fascinating advantages over model group in improving sleep. Moreover, the levels of GABA, Glu, 5-HT and DA factors of insomnia rats in brain were also monitored via ELISA method to further study the improving sleep mechanism of ZSSE. The results indicate that sleep could be improved effectively via up-regulation of GABA and 5-HT, and down-regulation of Glu and DA, respectively. In addition, molecular mechanisms of ZSSE in improving sleep were also studied by immunohistochemical analysis. The results indicate sleep could be improved by regulating the expression levels of GABAARα1 and GABAARγ2 receptors in hypothalamus and hippocampus tissue sections. Therefore, this work not only identifies the active ingredients of ZSSE, but also reveals the potential pharmacological mechanism of ZSSE for the improving sleep, which may greatly stimulate the prospective development and application of ZSSE.